PUBLIC ADMINISTRATION OF PERSONAL FULFILLMENT IN SPORTS: SOCIO-PHILOSOPHICAL ASPECT - Rybchych I.Ye. (Pressing Problems of Public Administration, 2015)
The phenomenon of sports as a tool for communication and socialization in the system ofpublic-authority relations has been researched. The purpose of sports to motivate people todisclose their essential forces has been studied. The main aspects of public administration processof getting people involved in athletic sporting activities have been found out.